Description of the Elbow Joint Range of Motion in Tennis Elbow Sufferers in the Badminton Community PB. Lalu Lalang Banjarbaru - Ira Malawaty; Arfian Hamzah; Enny Fauziah (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2024)
Tennis elbow characterized by the emergence of pain around the elbow that often occurs in tennis players causing the tendons extensor wrist length epicondylus lateral and radiohumeral joint pain from gripping. This study aims to find out the description range of motion elbow joint in suffererstennis elbow in PB. Lalu Lalang Banjarbaru Community. This study uses a type of quantitative research with a descriptive research design conducted to determine the value range of motion (ROM) using a gonometry. The research results obtained were mostly at the age of 31-40 years (52%), male sex at most with a total of 15 people (88%), the frequency of exercise was at most 7 people 2x/week (41%), andrange of motion elbow obtained the average in the extension movement is 3°, in the flexion movement is 150°, in the supination movement is 87°, and in the pronation movement is 89°.